2019
DOI: 10.1186/s13024-019-0338-0
|View full text |Cite
|
Sign up to set email alerts
|

Neurofilament light chain is a promising serum biomarker in spinocerebellar ataxia type 3

Abstract: BackgroundSpinocerebellar ataxia type 3 (SCA3) is the most common subtype of autosomal dominantly inherited spinocerebellar ataxias (SCAs). No validated blood biomarker is available to assess either disease progression or therapeutic response. Neurofilament light chain (NfL) was recently proposed as a serum biomarker for many neurodegenerative disorders. The present study investigated whether NfL was a promising serum biomarker for SCA3.MethodsSeventeen SCA3 patients and 9 controls were enrolled in cohort A, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
98
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(109 citation statements)
references
References 31 publications
11
98
0
Order By: Relevance
“…Nfs and mutant ataxin-3 might thus overall serve as complementary biomarkers in preclinical SCA3 mouse treatment trials. Taken together, these comprehensive findings of our study largely extend recent preliminary findings from our and other labs (Wilke et al, 2018;Li et al, 2019) which suggested NfL increases in human SCA3, but were limited to non-multicentric, single-assay, human-only NfL studies, which also lacked the comparative assessment of NfL and pNfH and the biomarker cascade mapping.…”
Section: Discussionsupporting
confidence: 83%
“…Nfs and mutant ataxin-3 might thus overall serve as complementary biomarkers in preclinical SCA3 mouse treatment trials. Taken together, these comprehensive findings of our study largely extend recent preliminary findings from our and other labs (Wilke et al, 2018;Li et al, 2019) which suggested NfL increases in human SCA3, but were limited to non-multicentric, single-assay, human-only NfL studies, which also lacked the comparative assessment of NfL and pNfH and the biomarker cascade mapping.…”
Section: Discussionsupporting
confidence: 83%
“…Biomarkers serve as a potential diagnostic feature in addition to providing insight into disease progression. Current biomarker candidates such as Neurofilament Light Chain are increased in ALS patients and may provide insight into disease progression, but is non-specific to ALS and only provides foresight by about 12 months before symptoms occur [269][270][271][272][273]. As TDP-43 mislocalization is a central feature in ALS and biomarkers based on phenotypes associated with mislocalization may provide the specificity and foreshadowing required for early diagnosis.…”
Section: Approaches To Study Tdp-43 Mislocalization To Better Understmentioning
confidence: 99%
“…Therefore, it is crucial that newly established biomarkers are disease specific and that there is a correlation between surrogate and clinical endpoints [16]. As for many other neurodegenerative diseases, neurofilament light chain (NfL) is shown to be increased in preataxic mutation carriers already 7.5 years before disease onset also in SCA3 even correlating with disease severity [17][18][19]. However, NfL only reflects general axonal damage which captures disease progression and disease severity and, therefore, acts as a progression and severity biomarker.…”
Section: Introductionmentioning
confidence: 99%